Implementation of Location Planning in Improving the Success of Local Retail Business: a Case Study of Citra Shoes, Solok City - Yulia Wulan Dhari; Ana Frehesti; Lusiana Lusiana (Sean Institute, 2026)
This study aims to analyze the implementation of location planning in increasing the success of local retail businesses using a case study of Citra Shoes in Solok City. The research method used is a descriptive qualitative approach, which aims to describe in depth the phenomena occurring in the field. Data collection techniques were carried out through direct observation, interviews with owners and customers, and documentation related to business activities. The results of the study indicate that strategic location selection has a significant influence on increasing the number of customers and sales turnover. Locations that are easily accessible, clearly visible from main roads, and located in areas with high traffic levels tend to attract more consumers. In addition, proximity to centers of economic activity such as markets, offices, and public facilities also contribute to business success. Careful location planning allows businesses to maximize existing market potential. Thus, it can be concluded that the right location strategy is one of the important keys to increasing the competitiveness and sustainability of local retail businesses amidst increasingly fierce competition.